The Pattern of Financial Management and Challenges Faced by Digital Startups in Indonesia: an Accounting and Financial Technology Perspective - Halim, Ade Imam Muttaqien; Muhammad, A Fadel; Nitswat, Nurhaliza; Ardi, Nur Astiana Hidayat (Economics and Business Journal (ECBIS), 2025)
This research aims to explore the financial management patterns applied by digital startups in Indonesia, along with the challenges and solutions faced by their founders in managing their finances. The study uses a qualitative approach with case studies to gather data through in-depth interviews, observations, and analysis of financial documents from digital startups operating in Indonesia. The findings reveal that ineffective cash flow management, dependence on external funding, and a lack of strategic financial management understanding are some of the primary challenges faced by these startups. The study emphasizes the importance of adopting efficient financial practices, including utilizing financial technology to improve cash flow management and reduce dependency on external capital. Additionally, it underscores the need for startup founders to build a competent finance team to ensure sustainable growth. This research contributes to the understanding of financial management in the context of digital startups in Indonesia and provides insights on overcoming financial challenges to strengthen the startup ecosystem